How to Grow a Magic Tree and Prosper from it (Part 4) - Puteri Fadzline, Muhamad Tamyez (livingmsia, 2017)
AGARWOOD IS SUCH A SPECIAL TREE and mysterious altogether. This magic tree has been in a hot seat for over 2000 years, from appearing in old texts and transcripts, continuing to be widely used in almost all cultures in the Asian region, to being one of the most important base notes in modern perfumery. Indeed it has remained the mainstay product allowing anyone to transform into a million-dollar corporate entity.